The Exploration And Identification Morphological Character Of Torch Ginger In Solok District West Sumatra Province - Rachmad Hersi Martinsyah (JERAMI : Indonesian Journal of Crop Science, 2021)
Torch ginger is one of the spices used as food and traditional medicine which is rich in antioxidants. However, the existence of this plant is decreasing every year, especially in Solok district, West Sumatra province. So it is necessary to explore and identify the morphology of kecombrang plants in Solok district, West Sumatra province. The research was conducted by exploring and analyzing the similarity clusters with the Minitab 16 application. The purpose of this study was to collect germplasm and study the morphological characters and similarities of tourch ginger plants in Solok district, West Sumatra province. The exploration results obtained 20 kecombrang plant accessions from 8 locations in Solok district. Kinship or similarity level obtained 2 clusters. The differences between the two plant clusters were indicated by the similarities and differences in morphological characters in the stem color, leaf edge color and flower stem color. The similarity value obtained is 0.22-1.00, which means the highest similarity is 100% and the lowest is 22%